High-power UV-LED degradation: Continuous and cycled working condition influence. (September 2015) - Arques-Orobon, F.J.; Nuñez, N.; Vazquez, M.; Segura-Antunez, C.; González-Posadas, V.
Graphical abstract: Highlights: 4000 h ALT for 3 W UV-LED in continuous and cycled working condition were conducted. Silicone package degradation (cracking) is the origin of light degradation failure. A set of possible solutions to mitigate package degradation have been proposed. Average failure time in cycled mode is two to three times larger than in continuous. Abstract: High-power (HP) UV-LEDs can replace UV lamps for real-time fluoro-sensing applications by allowing portable and autonomous systems. However, HP UV-LEDs are not a mature technology, and there are still open issues regarding their performance evolution over time. This paper presents a reliability study of 3 W UV-LEDs, with special focus on LED degradation for two working conditions: continuous and cycled (30 s ON and 30 s OFF). Accelerated life tests are developed to evaluate the influence of temperature and electrical working conditions in high-power LEDs degradation, being the predominant failure mechanism the degradation of the package. An analysis that includes dynamic thermal and optical HP UV-LED measurements has been performed. Static thermal and stress simulation analysis with the finite element method (FEM) identifies the causes of package degradation. Accelerated life test results prove that HP UV-LEDs working in cycled condition have a better performance than those working in continuous condition.